Tuning the cell fate of neurons and glia by microRNAs - Bian, Shan (2013)
The proper function of the nervous system depends on precise production and connection of distinct neurons and glia. Cell fate determination of neurons and glia is tightly controlled by complex gene expression regulation in the developing and adult nervous system. Emerging evidence has demonstrated the importance of noncoding microRNAs (miRNAs) in neural development and function. This review highlights current discoveries of miRNA functions in specifying neuronal and glial cell fate. We summarize the roles of miRNAs in expansion and differentiation of neural stem cells, specification of neuronal subtypes and glial cells, reprogramming of functional neurons from embryonic stem cells and fibroblasts, and left-right asymmetric organization of neuronal subtypes. Investigating the network of interactions between miRNAs and target genes will reveal new gene regulation machinery involved in tuning the cell fate decisions of neurons and glia.